2018
DOI: 10.1159/000486812
|View full text |Cite
|
Sign up to set email alerts
|

Risk of de novo Hepatocellular Carcinoma after HCV Treatment with Direct-Acting Antivirals

Abstract: Background and Aims: The aim of the study was to evaluate the risk of hepatocellular carcinoma (HCC) development after treatment with direct-acting antivirals (DAAs) and to compare HCC occurrence in these patients with that among patients treated with interferon (IFN)-based therapies. Methods: We analyzed a large cohort with chronic hepatitis C virus patients for the onset of new HCC after DAA treatment. A historical IFN-treated cohort was investigated for comparison. Results: A total of 819 patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…This immunologic hypothesis may be of further interest regarding the ongoing debate whether treatment of HCV infection with DAAs could potentially even increase the risk of HCC occurrence and recurrence compared to interferon (IFN)‐based treatments . However, as we have recently shown, there is a growing body of evidence that HCC occurrence and recurrence rates do not increase but even decrease following DAA therapy and are comparable to those reported in the IFN era . Nahon et al recently pointed out, that age, diabetes and reduced liver functions, as well as different screening intensity can explain the apparent increase of HCC incidence in patients after DAA‐therapy compared to patients who received IFN therapy .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This immunologic hypothesis may be of further interest regarding the ongoing debate whether treatment of HCV infection with DAAs could potentially even increase the risk of HCC occurrence and recurrence compared to interferon (IFN)‐based treatments . However, as we have recently shown, there is a growing body of evidence that HCC occurrence and recurrence rates do not increase but even decrease following DAA therapy and are comparable to those reported in the IFN era . Nahon et al recently pointed out, that age, diabetes and reduced liver functions, as well as different screening intensity can explain the apparent increase of HCC incidence in patients after DAA‐therapy compared to patients who received IFN therapy .…”
Section: Discussionmentioning
confidence: 76%
“…39,40 However, as we have recently shown, there is a growing body of evidence that HCC occurrence and recurrence rates do not increase but even decrease following DAA therapy and are comparable to those reported in the IFN era. 41 Despite of our promising new data, our current study had some limitations. We analysed SL concentrations in a retrospective setting and therefore we cannot prove underlying mechanistical relationships.…”
Section: Discussionmentioning
confidence: 84%
“…Fibrosis becomes more harmful and progresses to liver cirrhosis [16] . Most HCV-associated hepatocellular carcinoma is seen with experience of liver fibrosis or cirrhosis [17] . Recent options of HCV treatment as DAAs can efficiently eradicate the virus, but regression of hepatic fibrosis in all patients is not the same.…”
Section: Discussionmentioning
confidence: 99%
“…SVR rates varies for particular genotypes, that is, genotype 1 shows around 42‐58%, genotype 2 shows 80%, genotype 3 and 4 shows 66% or 63‐69%, respectively . However, some studies have reported that recurrence of HCC in chronic hepatic patients even after they achieve SVR in DAA treatment …”
Section: Hcv Treatmentmentioning
confidence: 99%